Sexual Health and Masculinity: Examining the Stigma around Reproductive Health Services for Middle-Aged Men in Cameroon - Ikhile, Ikekhwa Albert (Journal of Ecohumanism, 2025)
Background: Masculinity norms shape health-seeking behaviors, often discouraging men from accessing reproductive health services. In Cameroon, middle-aged men face stigma when seeking such care, exacerbating unmet health needs. This study explores how masculinity influences stigma and access to reproductive health services among middle-aged men in Cameroon. Methods: A combination of quantitative survey data from 60 men (n =60) and qualitative in-depth interviews from 20 participants (n =20) was collected from men aged 35–55 who resided in urban and rural areas of Cameroon. Research data underwent both descriptive and inferential statistical analysis for quantitative information and thematic analysis was used for qualitative data assessment. Results: Findings indicate that hegemonic masculinity reinforces stigma, deterring men from seeking reproductive health services. Self-stigma creates avoidance in healthcare by making males uneasy about representations of weakness and social stigma arises from cultural pressures that discourage men from using reproductive health services. The healthcare system carries its own stigma which healthcare providers express through negative behaviors to put more barriers before men wishing to access reproductive services. Men embracing stigma use separate approaches which include self-treating their issues alongside hiding their problems and trusting non-medical healthcare providers. Conclusion: Masculinity-driven stigma creates systemic barriers to reproductive healthcare for middle-aged men in Cameroon. Effective solutions to overcome this problem demand healthcare systems that view gender differences and also need community-based approaches along with stigma reduction programs in health facilities. Strengthening male-inclusive reproductive health services could improve health outcomes and challenge restrictive gender norms.